Supply chain management program at Clarkson University: a systems approach. (9th January 2006) - Mahmoodi, Farzad; Wasserman, Michael E.; Pant, Somendra
This article traces the development of the Clarkson University supply chain management (SCM) program. This program, which takes a systems approach, has achieved national recognition in recent years, earning a rating as one of the top SCM undergraduate programs in the nation by US News & World Report in 2003, 2004 and 2005. The emphasis of this paper is on the systems approach and its influence on the curriculum, executive programs, faculty research and student projects. We offer conclusions and lessons learned that may be valuable to small schools wishing to build or strengthen an SCM program.